A modified procedure for the evaluation of the amylose and amylopectin content in potato starch - Yu. A. Khoroshavin (Vavilovskij Žurnal Genetiki i Selekcii, 2018)
The article is devoted to the development of a technique for determining the content of amylose and amylopectin, effective for potato starch. Since potato starch is an important renewable raw material for a number of industries, it is important to have a throughput approach that allows potato starch samples to be tested quickly for the content of its constituent polysaccharides for potato breeding for starch properties and for starch industrial application. The developed technique includes elements of previously disjointed procedures for dissolution and spectrophotometric determination of amylose in starch, and combines the following advantages: 1) starch samples dissolve in an organic solvent (0.5 % solution of lithium bromide in dimethyl sulfoxide (DMS)); 2) measurement of light absorption is performed at two wavelengths, 550 and 510 nm, and 3) the technique is adapted for use with a plate spectrophotometer. This procedure allows starch polysaccharides to avoid to avoid hydrolysis during dissolution, allows the precise spectrophotometric determination of the concentration of amylose complex with iodine in solution, and opens the possibility of using this technique for throughput phenotyping. Applying a certain dissolution procedure, it is also possible to avoid the formation of gelled starch clots in solutions for spectrophotometry, which is important for the preparation of solutions containing amylose and amylopectin in the same proportions as in the original starch. The technique was tested on starch isolated from potato tubers varieties Lina, Velikan, Golubizna, Favorit of domestic selection. The technique developed can be used for phenotyping starch of an extended set of potato varieties (determining the content and composition of amylose in potato starch samples) to identify "trait-genotype” associations.